Fostering Chemistry Students’ Scientific Literacy for Responsible Citizenship through Socio-Scientific Inquiry-Based Learning (SSIBL) - Georgiou, Yiannis; Kyza, Eleni A. (My University, 2023)
Fostering secondary education students’ responsible citizenship and preparing them to be critically engaged with global socio-environmental challenges are of crucial importance toward achieving sustainability. This paper contributes to the effort to understand how to support students’ scientific literacy for responsible citizenship by reporting on a study evaluating the impact of a learning intervention on biofuels, structured upon Socio-Scientific Inquiry-Based Learning (SSIBL) pedagogy. The participants were 93 students in secondary chemistry education; these students were assigned to the SSIBL group (n = 46) or to the control group (n = 47), which participated in Business-As-Usual (BAU) instruction. Quantitative data were collected with the Global Scientific Literacy Questionnaire (GSLQ) before and after the learning intervention for evaluating students’ perceptions of science as a human endeavor (i.e., nature of science), as well as their personal responsibility and willingness to take action for maintaining a sustainable environment (i.e., values and attitudes). Qualitative data were also collected through video recordings of the SSIBL implementation to examine how the SSIBL instruction was enacted. The findings indicated that, after the implementation, students in the SSIBL condition outperformed their counterparts in the control condition. These findings provide empirical documentation supporting the use of the SSIBL learning intervention to foster students’ scientific literacy for responsible citizenship. The video recordings also shed light on how the SSIBL instruction phases (i.e., Ask, Find out, Act) contributed to the development of students’ responsible citizenship, as a pre-requisite for achieving sustainability.
Keywords: chemistry education; responsible citizenship; scientific literacy; Socio-Scientific Inquiry-Based Learning (SSIBL); sustainability